KEDUDUKAN ANAK PEREMPUAN DALAM PEWARISAN MENURUT HUKUM ADAT NIAS SELATAN DI KECAMATAN MANIAMOLO - Dakhi, Albertus (JURNAL PANAH KEADILAN, 2024)
Based on the problem formulation above, the aim of this research is to determine and analyze the position of girls in inheritance according to South Nias customary law in the Maniamolo sub-district. Customary inheritance law is the totality of legal regulations and customary guidelines, which regulate the transfer and succession of inherited assets with all the consequences, whether carried out while the testator is still alive or after he dies. Customary inheritance law is closely related to customary family law and customary marriage law. The legal status of women's rights to inheritance is problematic in partial relationships. This is because women are human beings created by God who have the same position as boys. Inheritance Law is the law that regulates the position of a person's assets after he or she dies (the heir), and the methods by which the assets are transferred to other people (the heirs). Customary Law is the totality of rules or norms, both written and unwritten, originating from the customs or customs of society. The data analysis carried out was descriptive qualitative analysis and conclusions were drawn using a deductive method. This research uses a type of sociological legal research or empirical legal research. Sociological legal research is also called legal research which obtains data directly in the field or where the research is conducted. The data needed in the research is primary data. The aim of sociological legal research aims to prove an allegation by making observations and experiments to find the truth. Specification is a solid phase extraction method that can be used for analysis, separation, purification of samples in the pharmaceutical industry, as well as toxicological analysis such as blood, serum, liquids and food. Based on the research findings and discussion, the conclusions that can be drawn are: The position of girls in inheritance according to South Nias customary law in Maniamolo District, that according to customary law girls have the right to inherit. The position of girls in inheritance has the same rights. with men, but the inheritance is greater for sons than daughters, and the position of daughters is also stronger if their brothers are not present, and are responsible for the existing customary position.